Preoperative bimodal imaging evaluation in finding histological correlations of in situ, superficial spreading and nodular melanoma - Negrutiu, Mircea; Danescu, Sorina; Popa, Theodor; Rogojan, Liliana; Vesa, Stefan Cristian; Baican, Adrian (Frontiers in Medicine, 2024)
Background: The aim of this study is to correlate the diagnostic criteria described in dermoscopy, ultrasonography (US), and histology of the most common types of cutaneous melanoma (CM). Methods: We conducted a prospective study including 40 CM cases, which were analysed by dermoscopy using the Delta 30 dermatoscope and Vidix 4.0 videodermoscope, by ultrasound (US) using a high-resolution 20MHz linear probe, along with histopathological analysis. Results: The study involved 40 patients with histopathologically confirmed CM, comprising 10 nodular melanomas (NM), 21 superficial spreading melanomas (SSM), and 9 in situ melanomas (MIS). US measurements of tumour thickness exhibited strong correlations with the histopathological Breslow index (BI), particularly in the NM and SSM groups. A notable correlation was observed between the presence of ulceration in histopathology and ultrasonography. Dermoscopic analysis revealed significant associations between specific features and CM types. For instance, the presence of an atypical network, irregular globules, irregular dots, prominent skin margins, angulated lines/polygons, dotted and short linear vessels, and negative network correlated with a median BI <= 0.5 mm. Conversely, the presence of blue-white veil, atypical vessels, blue-black color, and milky red color were associated with a median BI >= 2.3 mm. Furthermore, regression observed in histopathology correlated with regression identified in dermoscopy We also found statistical correlations between the presence of vascularization at US with the high Clark level, and the presence of prominent skin markings at dermoscopy. The presence of histopathological regression was more frequently associated with tumors that had precise margins, absent vascularization and with those that did not have ulceration on US. The high mitotic rate was associated with tumors that presented imprecise margins, increased vascularization and US detectable ulceration. Conclusion: Innovative CM diagnosis using non-invasive methods like dermoscopy and ultrasound may enhance accuracy and treatment guidance by assessing lesion characteristics.